The influence of green hospitality implementation and hotel image on guest loyalty at Grand Mercure Hotel Medan - Sihombing, Daniel (International Journal of Applied Finance and Business Studies, 2025)
This study aims to analyze the effect of Green Hospitality implementation and hotel image on guest loyalty at the Grand Mercure Hotel Medan. The background of this study is based on the increasing consumer awareness of sustainability issues in the hotel industry, as well as the importance of corporate image in shaping customer loyalty. The research method used is a quantitative approach with multiple linear regression analysis techniques, using primary data obtained from 97 respondents through a Likert-scale questionnaire. The results of the partial test indicate that both Green Hospitality implementation and hotel image have a significant effect individually on guest loyalty. The simultaneous test (F test) also shows that both variables together have a significant effect on guest loyalty. The coefficient of determination (R²) value of 0.273 indicates that 27.3% of the variation in guest loyalty can be explained by the combination of the two variables. This study strengthens the urgency of integrating green strategies and corporate image as a strategic approach to increasing customer retention. The managerial implication is that strengthening sustainability values and positive institutional image can be a relevant competitive differentiation in the era of increasingly environmentally conscious modern tourism.